"Give it a Try": experiences of black, Asian and minority ethnic young men in a prison-based offender personality disorder service. Issue 1 (31st January 2019) - Hunter, Stephanie; Craig, Eleanor; Shaw, Jake
Abstract : Purpose: Within the current offender personality disorder (OPD) pathway in the UK, black, Asian and minority ethnic (BAME) populations are underrepresented. Fewer BAME offenders are engaging with services despite being proportionately identified for inclusion and referred on to the pathway. The paper aims to discuss this issue. Design/methodology/approach: This qualitative study explored the experiences of 11 BAME men engaged in a prison-based OPD service for young offenders to identify the highlights and challenges of engagement within the service and to what extent they experienced a sense of inclusion/belonging. Findings: Thematic analysis was used to identify three overarching themes and sub-themes. Why am I going to be an Outcast? describes the barriers to engagement encountered by the participants; and Give it a Try and Nothing but Respect describe the process of overcoming these barriers. Barriers revolved around the experiences of judgement, alienation and hopelessness. These were overcome through peer encouragement, developing relationships with staff and freedom to regulate levels of engagement. Practical implications: Practice and policy implications are considered to support similar services in addressing the barriers to engagement faced by BAME individuals. Areas for future research are also recommended. Originality/value: Currently, no research has directly explored the under-representation of young BAME offenders with emerging personality disorder in the OPD pathway. The findings provided an insight into some of the difficulties these young BAME offenders faced when accessing this service, alongside aspects which maintained their engagement.